Pelatihan Pembelajaran Google Meet Bagi Guru di UPTD SD Negeri 15 Padang Genting Kabupaten Batubara - Siregar, Yunita Sari; Herlina Harahap; Nenna Irsa Syahputri; Divi Handoko; Dedy Irwan (Jurnal Pengabdian Masyarakat, 2022)
In the era of increasingly developing technology, the use of computers is not only used to facilitate work in offices, but can be used as a medium of learning in the classroom for teachers. There are many applications on computers that can be used to support the teaching and learning process of students in schools such as media provided by Google. Google is one of the largest providers of web facilities with various online learning applications such as google classroom, google docs, google meet, jamboard and so on. This community service activity was carried out at the UPTD SD Negeri 15 Padang Genting, Batubara Regency by utilizing the Google Meet media, where the participants in this activity were 12 teachers. The purpose of this activity is to add insight, knowledge for teachers in teaching and learning activities and the effectiveness of time to be able to keep getting knowledge and material from teachers in schools. The results of this training activity are expected that teachers can improve the utilization and use of information technology as a learning medium and know the function of the tools provided by Google Meet.